PERENCANAAN SISTEM PENYALURAN AIR LIMBAH (SPAL) DAN INSTALASI PENGOLAHAN AIR LIMBAH (IPAL) UNTUK INDUSTRI TEPUNG SAGU AREN DI DESA PLAJAN - Naelis Aprilianti, Eka; Rochmanto, Decky; Adi Saputro, Yayan; Khitam, Akhmad Firdos Khoiril; Maulana Ismail, Naufal; Khayatul Akbar, Muhamad; Bintang Putra Rohim, Arsweindo (SAINTIS Jurnal ilmu-ilmu eksakta, 2025)
The sago palm flour industry in Plajan Village generates wastewater containing pollutant concentrations that exceed the permitted quality standards and is still directly discharged into nearby water bodies. This study aims to design a wastewater conveyance system (SPAL) and a wastewater treatment plant (IPAL) that are appropriate for the characteristics of sago industry wastewater. The planning method is based on wastewater flow analysis, wastewater quality characteristics, and the biological design of IPAL units, referring to the Regulation of the Minister of Environment Number 5 of 2014 and relevant wastewater treatment design literature. The results show that the peak wastewater discharges are 19.38 m³/day and 17.24 m³/day for each industry, with a total SPAL network length of 80 m using PVC pipes with diameters of 5 and 6 inches. The planned IPAL units consist of an equalization tank, anaerobic digester, primary sedimentation tank, anaerobic biofilter, aerobic biofilter, and final sedimentation tank, with a total estimated cost of IDR 183,033,461.08.